(untitled) (Scientific journal of the Fergana State University, 2023)
The article focuses on the military situation in the Bukhara Emirate in the XIX century from the Central Asian states, their methods of armament, the system and essence of military-administrative management. During this period, Central Asian countries lagged behind the developed world in terms of military armaments and military tactics, according to archival and important sources. The article notes the reforms implemented by some heads of state in the 19th century in order to preserve the country’s independence and territorial integrity in the face of growing internal and external threats.